Joaquim Martí i Gadea com a lexicògraf i com a dialectòleg - Colomina i Castanyer, Jordi (Caplletra. Revista Internacional de Filologia, 2015)
The work of Joaquim Martí i Gadea, born in Alcoi, and mainly known as a folklorist as well as the founder of Valencian Dialectology, has plenty to offer to the modern lexicographer.